Numerical Investigation On The Aerodynamics Of Vertical Axis Hydrokinetic Turbines With Semi-Empirical Data - Foong, Xipeng (Universiti Sains Malaysia, 2018)
Renewable energy sources provide a sustainable power production for the future. Hydropower is one of the optimum choices for renewable energy extraction. Predictability, regularity and reliability make hydropower the most attractive choices for energy production. Hydrokinetic energy is harnessed from flowing streams, tidal currents and other water channels. Compared to conventional hydropower, construction of a dam or reservoir is not required due to its nature of extracting energy via water motion. Hydrokinetic turbines can be divided into two main categories: horizontal axis turbines and vertical axis turbines. For this project, attention is given to vertical axis hydrokinetic (VAHTs), due to the prominence in research of horizontal axis turbines and lack thereof for vertical axis ones. VAHTs are further classified according to their different arrangements: squirrel-cage Darrieus, H-Darrieus, Curved Darrieus, Gorlov and Savonius. In this project, the H-Darrieus turbine is chosen as the model to be investigated due to its utilization of airfoil-shaped blades, thus easing the calculation of forces. For the sake of creating a mathematical model, new theories related to VAHTs are learned. Some computational models are introduced briefly, but they are not used in this investigation. Also, some previous studies which are related to the project are highlighted. Next, design methodology is prepared to aid the mathematical modelling process. The airfoil data is extracted from a previous study (s1210, NACA-0015 airfoil). The mathematical model required to compute turbine performance is formulated and shown in steps. The initial parameters are also listed. Then, details regarding the modification of initial parameters, the in-depth study of tip speed ratio and turbine solidity, and the investigation of self-starting physics are outlined. In the end, all data acquired are displayed and plotted according to the requirements of the project. First, a baseline plot of one-blade configuration is introduced to provide a basis for comparing results. Then, plots of two-blade and three-blade turbines are made and compared to the one-blade turbine results. An in-depth look into the tip speed ratio and turbine solidity reveals that they affect the turbine similarly in outcomes but differs a little in the process. A brief insight into the self-starting physics and issues of VAHT is provided and suggestions on improving the self-starting of turbines are given. The project is then concluded with the summarization of previously covered stuff, the drawing of conclusions based on the observations and inferences, as well as suggestions provided to improve the current project and ideas for new advanced projects that can be taken in the future.